PENGEMBANGAN MAJALAH DINDING DIGITAL (MADIDI) DI WEBSITE SEKOLAH SEBAGAI SARANA PUBLIKASI PRODUK PEMBELAJARAN BAHASA INDONESIA - Alfanny Pratama Fauzy; Munaris Munaris; Rahmat Prayogi (FKIP Universitas Lampung, 2021)
This research is conducted to study the development of Majalah Dinding Digital (Madidi) on a school website and its feasibility as a means of publishing Indonesian learning products at MAN 2 Bandarlampung. The method used in this research is the research and development (RD) method. Data sources used form of interviews, observations, and feasibility of learning experts, media experts, Indonesian language teacher, and the results of trials of journalistic extracurricular administrators. The results of this research and development are a digital wall magazine that can be accessed at Madidi.id. Madidi developed is considered feasible based on the results of validation by learning experts with a score of 88%, media experts 80%, Indonesian language teacher 100%, and the results of trials by journalistic extracurricular administrators 94.4%. Based on the results of research and development that have been carried out, Madidi developed is worthy of being a means of publishing Indonesian language learning products at MAN 2 Bandarlampung.Penelitian ini dilakukan untuk mengetahui pengembangan majalah dinding digital (Madidi) di website sekolah dan kelayakannya sebagai sarana publikasi produk pembelajaran bahasa Indonesia di MAN 2 Bandarlampung. Metode yang digunakan dalam penelitian ini adalah metode Research and Development (RD). Sumber data yang dipakai berupa hasil wawancara, observasi, dan kelayakan dari ahli pembelajaran, ahli media, pendidik bahasa Indonesia, serta hasil uji coba pengurus ekstrakurikuler jurnalistik. Hasil penelitian dan pengembangan berupa majalah dinding digital yang dapat diakses dengan laman madidi.id. Madidi yang dikembangkan tergolong layak berdasarkan hasil validasi ahli pembelajaran dengan nilai 88%, ahli media 80%, pendidik bahasa Indonesia 100%, dan hasil uji coba pengurus ekstrakukrikuler jurnalistik 94,4%. Berdasarkan hasil penelitian dan pengembangan yang telah dilakukan, Madidi yang dikembangkan layak menjadi sarana publikasi produk pembelajaran bahasa Indonesia di MAN 2 Bandarlampung.Keywords: development, learning, madidi, wall magazine.DOI: http://dx.doi.org/10.23960/Kata.v9.i2.202103